Peningkatan Branding UMKM Opak Jepit Melalui Pelatihan Food Photography - Muqit, Abd.; Sulasari, Ayu; Unarto, Tirto; Maulidina, Ahsani; Rachmawati, Rina; Sinatrya, Jatrifia Ongga (Universitas Muhammadiyah Mataram, 2025)
Abstract: The owner of Opak Jepit Mekar Sari MSME has struggled for years to learn how to utilize the right digital strategies to enhance her business branding. The primary objective of this activity is to enhance the branding of partner MSMEs by leveraging information technology through effective marketing management, through training in food photography techniques. The method used in implementing this activity is training and mentoring, which is carried out through several stages: planning, preparation and coordination, training in the use of food photography techniques for product marketing, mentoring in designing packaging labels, mentoring the marketing system through the creation of an Instagram social media account, and joint evaluation. The results of this activity can be used as packaging labels or marketing materials on social media.Abstrak: Pemilik UMKM Opak Jepit Mekar Sari telah berjuang selama bertahun-tahun untuk mempelajari cara memanfaatkan strategi digital yang tepat guna meningkatkan branding bisnisnya. Tujuan utama kegiatan ini adalah untuk meningkatkan branding UMKM mitra dengan memanfaatkan teknologi informasi melalui manajemen pemasaran yang efektif melalui pelatihan teknik food photography. Metode yang digunakan dalam pelaksanaan kegiatan ini adalah pelatihan dan pendampingan, yang dilakukan melalui beberapa tahapan: perencanaan, persiapan dan koordinasi, pelatihan pemanfaatan teknik fotografi makanan untuk pemasaran produk, pendampingan dalam mendesain label kemasan, pendampingan sistem pemasaran melalui pembuatan akun media sosial Instagram, dan evaluasi bersama. Hasil kegiatan ini dapat digunakan sebagai label kemasan maupun materi pemasaran di media sosial.